Tratamiento y profilaxis antibiótica de patologías comunes en ginecología- obstetricia - Sandoval Z. , Jorge; Fica C., Alberto; Caballero T., Rafael (Revista Hospital Clínico Universidad de Chile, 2008)
A literature review was performed looking for rational evidence for some common antibiotic prescriptions in gynecology and obstetrics. Conditions that deserve a therapeutic indications include asymptomatic bacteriuria , bacterial vaginosis or vaginitis during pregnancy, urinary tract infections and some recurrent urinary tract infections, postpartum endometritis, pelvic inflammatory disease, and listeriosis. In the same manner, prophylactic interventions with antibiotics are warranted before a cesarean section, abdominal or vaginal histerectomy, as well as during preterm labour with rupture of membranes or due to a presumed or demonstrated group B Streptococcus carriage. On the other hand, antibiotic use during preterm labour with intact membranes, while inserting or removing an intrauterine device or by an incomplete asymptomatic abortion, is not supported by scientific evidence. Finally, information is lacking for an antibiotic indication in fourth-degree perineal tear or during instrumental vaginal delivery.